The influence of male dominance in female Anastrepha curvicauda mate selection - Nancy Natividad Salmerón-Muñiz (Nature Portfolio, 2021)
Abstract Males of the papaya fruit fly, Anastrepha curvicauda Gerstaecker (former Toxotrypana curvicauda), defend a papaya fruit from rivals and males release their sex pheromone to attract and mate with females and offer them an oviposition site. While some aspects of the biology of A. curvicauda are known, such as its reproductive biology, its sex pheromone, and host selection, there is currently no information on the species mate selection process. This paper describes the precopulatory mating behavior of A. curvicauda and elucidates how intrasexual selection affects the mate selection process. We studied the precopulatory mating behavior of dominant and subordinate males and ethograms were devised. The effect of hierarchy was studied in non-choice and choice experiments. Male’s repertoire includes 15 behavioral elements, 12 precopulatory, one mating, and two postcopulatory (tandem and encounter). In non-choice experiments, dominant and subordinate males were accepted by females, but when females had the opportunity to choose among males, dominant males were significantly preferred over subordinate ones. The presence of a rival male modified the courting behavior of males and agonistic behavior among males was observed before and during mating.